Abjad kemuliaan 100 hari pertama Dato' Seri Abdullah Ahmad Badawi - Roslan Abdul Hamid (Penerbit Indah Abjad, 2004)
Challenges for Abdullah Ahmad Badawi in his first 100 days as Prime Minister of Malaysia.